Investigation of emissions and performance of diesel engine with the blend of Jatropha Diesterol Fuel using response surface methodology - Navab Kazemi; Seyed Mohammad Safieddin Ardebili; Niloofar Alizadehbehbahani (Advances in Environmental Technology, 2020)
In this research work, the performance and the exhaust emissions of a CI engine operating on diesel-biodiesel-ethanol blended fuels were investigated. The main purpose of this study aimed to reduce the various emissions produced by the new blended fuels.  The conventional transesterification reaction was carried out to produce biodiesel from Jatropha seeds. A one-cylinder, four-stroke CI engine was powered by green blended fuels at various engine speeds. Response surface methodology (RSM) was exploited to analyze the performance and exhaust emission parameters of a diesel engine in terms of fuel blends and engine speed. According to the results obtained, an engine speed of 2657 rpm, a biodiesel concentration of 10.26%, and an ethanol ratio of 2.21% were found to be the optimal values. The obtained experimental results showed that adding ethanol-biodiesel to pure diesel fuel increased the diesel engine's performance, including power and torque output. The results also showed that the CO2 emission increased 9.6 % while CO, NOX, and HC emissions in the biodiesel-ethanol-diesel fuel decreased 1.33%, 5%, and 26.1 %, respectively, compared to pure diesel fuel. The specific fuel consumption of the new blended fuel decreased by 6.9 % compared to pure diesel fuel.